Heterosis and Combining Ability Studies in Maize (Zea Mays L.). - Reddy, Gillella Chinna (1991)
A Diallel cross with 12 parents and resulting 66 F 1's were evaluated for heterosis and combining ability during 1987 and 1988. Differences among genotypes were significant for all characters. Genotype X Year interaction was significant for all traits except ear length. Average heterosis related to better parent was highest for plot yield, Kernel number per row, ear length and ear diameter. Heterosis was maximum in combinations involving parents of extreme grain type (dent X flint) and/or diverse geographical origin. Degree of heterosis was lowest in crosses of high yielding parents and vice-versa. SCA was relatively more important for all characters. Data on heterosis was in general agreement with variance component ratios of SCA and GCA and supported conclusions concerning the relative importance of SCA over GCA. Variance components for interactions involving SCA and years were consistently larger suggesting that SCA variance includes a considerable portion of genotype-environment interaction, apart from non-additive deviations. GCA effects were consistent from year to year while SCA effects were not. Graphical analysis on diallel data revealed that dominance and epistasis were important for most characters. A tendency of more number of dominant genes were associated with greater performance of characters (except plant and ear height) in the desirable direction. Most important yield components were ear diameter, ear length, number of kernels per row and lOOO-kernel weight. Yield components as well as maturity traits were positively interrelated among themselves, respectively. However, maturity characters were negatively correlated with most traits. Heritability estimates based on co-variance among relatives were generally in close agreement with estimates based on variance components confirming the results of combining ability analysis. Heterosis breeding, reciprocal recurrent selection or recurrent selection for SCA may be followed depending on the final objective.